PENGARUH PENGAWASAN KUALITAS BAHAN BAKU DAN BIAYA PRODUKSI TERHADAP JUMLAH HASIL PRODUKSI PADA PT DHARMA POLIMETAL Tbk. - Maesaroh, Maesaroh; Sa’adah, Muflihatus; Mukti, Muhi (The Asia Pacific Journal Of Management Studies, 2023)
The Influence of Monitoring the Quality of Raw Materials and Production Costs on the Total Production Results at PT Dharma Polimetal Tbk for the 2019-2022 Period. This study aims to find out data about the effect of quality control of raw materials, production costs on the amount of production at PT Dharma Polimetal Tbk. The method used in this study is a quantitative method with an associative approach. The population of this study is all data related to monitoring the quality of raw materials, production costs, and the amount of production at PT Dharma Polimetal Tbk. The sample used is raw material quality control data, production costs, and total production output for 42 months from 2019-2022. Data collection techniques used observation and secondary data and data analysis techniques using classic assumption tests and hypothesis testing with the help of the SPSS Ver 20 program. Based on the results of hypothesis testing using the t test and F test, it can be seen that partially monitoring the quality of raw materials affects the amount of production with a t value of 2.757 > 2.757 > t table 2.022 with a significance of 0.002; 0.05, production costs partially affect the amount of production with a calculated t value of 2,839 >; t table 2.022 with a significance of 0.001; 0.05. The results of the F test of monitoring the quality of raw materials and production costs simultaneously affect the amount of production with an F value of 13,900 > 13,900 > F table 3.24 with a significance of 0.000 > 0.05.